A Potential New Chalcopyrite Reference Material for Secondary Ion Mass Spectrometry Sulfur Isotope Ratio Analysis. Issue 3 (30th June 2020) - Li, Rucao; Xia, Xiao‐Ping; Chen, Huayong; Wu, Nanping; Zhao, Taiping; Lai, Chunkit; Yang, Qing; Zhang, Yanqiang
Abstract : Chalcopyrite is an important sulfide mineral in many types of ore deposits, but matrix‐matched chalcopyrite reference materials for microanalysis are lacking. A new natural chalcopyrite‐bearing specimen (HTS4‐6) was analysed in this study to investigate its potential as a reference material for microbeam sulfur isotope ratio measurement. Detailed textural examination and major element determination showed that the HTS4‐6 chalcopyrite grains have no growth rim or zoning. A total of 607 sulfur isotope ratio spot measurements with secondary ion mass spectrometry (SIMS) conducted on the cruciform sections, and over 120 randomly selected grains yielded highly consistent sulfur isotope ratio. The intermediate measurement precision for four measurement sessions of the 34 S/ 32 S measurement results was better than 0.39‰ (2 s ). Randomly selected chalcopyrite grains of HTS4‐6 were further analysed by LA‐MC‐ICP‐MS, which gave a mean δ 34 S value of +0.58 ± 0.38‰ (2 s, n = 95). The maximum variance (expressed as intermediate precision from SIMS and LA‐MC‐ICP‐MS measurements) is not worse than 0.39‰ (the SIMS value), indicating that HTS4‐6 chalcopyrite is a potential reference material for in situ microbeam sulfur isotope measurements. The mean δ 34 S value determined by gas source isotope ratio mass spectrometry (GS‐IRMS) is +0.63 ± 0.16‰ (2 s, n = 23), consistent with that derived by LA‐MC‐ICP‐MS, and can represent the recommended value for this potential reference material. Abstract : Key Points HTS4‐6 chalcopyrite is a potential reference material for in situ sulfur isotope measurement. Recommended δ 34 S value for HTS4‐6 chalcopyrite is 0.63 ± 0.16‰ (2 s ). δ 33 S and δ 36 S values of HTS4‐6 chalcopyrite are also determined.